2017
DOI: 10.1016/j.neuropsychologia.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

An fMRI study of visual hemifield integration and cerebral lateralization

Abstract: The human brain integrates hemifield-split visual information via interhemispheric transfer. The degree to which neural circuits involved in this process behave differently during word recognition as compared to object recognition is not known. Evidence from neuroimaging (fMRI) suggests that interhemispheric transfer during word viewing converges in the left hemisphere, in two distinct brain areas, an “occipital word form area” (OWFA) and a more anterior occipitotemporal “visual word form area” (VWFA). We used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 61 publications
3
20
0
Order By: Relevance
“…That is consistent with our conclusion that left VWFA-1 contains two spatial channels while VWFA-2 contains only a single channel. Strother et al (30,36) also found that the right posterior region was biased for the left hemifield, which is consistent with our finding that right VWFA-1 contained a single channel and was especially responsive when attention was focused to the left. Our results go further to show how this circuit responds to pairs of whole words, and to relate the multivoxel patterns to selective attention and task performance.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…That is consistent with our conclusion that left VWFA-1 contains two spatial channels while VWFA-2 contains only a single channel. Strother et al (30,36) also found that the right posterior region was biased for the left hemifield, which is consistent with our finding that right VWFA-1 contained a single channel and was especially responsive when attention was focused to the left. Our results go further to show how this circuit responds to pairs of whole words, and to relate the multivoxel patterns to selective attention and task performance.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have concluded that the anterior portion of wordselective VOTC is more sensitive to higher-level, abstract, lexical properties (17,22,24). Another research group studied how VOTC integrates both halves of a single word that are split between hemifields (30,36). They found that a posterior left VOTC region (the "occipital word form area," roughly 12 mm posterior to our VWFA-1) represented both halves of a word but maintained them separately.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have concluded that the anterior portion of word-selective VOTC is more sensitive to higher-level, abstract, lexical properties (Dehaene et al, 2004; Lerma-Usabiaga et al, 2018; Vinckier et al, 2007). Another research group studied how VOTC integrates both halves of a single word that are split between hemifields (Strother et al, 2016; Strother, Zhou, Coros, & Vilis, 2017). They found that left VWFA-1 (which they label the “occipital word form area”) represented both halves of a word but maintained them separately.…”
Section: Discussionmentioning
confidence: 99%
“…The first reason is that visual word processing involves interactions with phonological information, so that there is a strong push to process visually presented words in the hemisphere with the speech centre (usually the left hemisphere). Indeed, interhemispheric transfer from the non-language-dominant to the dominant hemisphere has been documented at the very first stages of visual word processing, in the occipital cortex and in the border region between the occipital and temporal cortex (Strother, Zhou, Coros, & Vilis, 2017;Van der Haegen, Cai, & Brysbaert, 2012). Although feedback from the frontal cortex is known to influence visual word processing up to the occipital cortex (Price & Devlin, 2011), it is unlikely that feedback from emotional brain centres could completely alter the information flow.…”
Section: Discussionmentioning
confidence: 99%